2006
DOI: 10.1007/s00784-006-0052-5
|View full text |Cite
|
Sign up to set email alerts
|

Enamel matrix derivative alone or in combination with a bioactive glass in wide intrabony defects

Abstract: This controlled clinical study investigated the clinical and radiographic outcome of wide intrabony periodontal defects treated by enamel matrix derivatives alone or in combination with a bioactive glass over a period of 8 months. Twenty-three chronic periodontitis patients, who received initial therapy and had radiographical interproximal defects with an associated probing depth of 6 mm or more and an intrabony component of at least 4 mm, were included. Each of the patients, contributing at least one intrabon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
82
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(85 citation statements)
references
References 38 publications
2
82
0
1
Order By: Relevance
“…These findings are in agreement with those reported in previous preclinical studies indicating a beneficial effect of GDF-5 on periodontal wound healing/regeneration [10,11,19]. On the other hand, the magnitude of clinical improvements appeared to be in the range of those obtained with other regenerative materials such as a recombinant plateletderived growth factor (rhPDGF BB) on a β-TCP carrier, an enamel matrix protein derivative alone or guided tissue regeneration either alone or combined with grafting materials [20][21][22][23][24][25][26][27]. Furthermore, it is also important to note that the results observed in the control group compare favorably with previous studies evaluating treatment of intrabony defects using flap surgery alone indicating that substantial clinical improvements may be achieved with this treatment modality if an optimal level of plaque control is maintained [21][22][23][26][27][28].…”
Section: Discussionsupporting
confidence: 81%
“…These findings are in agreement with those reported in previous preclinical studies indicating a beneficial effect of GDF-5 on periodontal wound healing/regeneration [10,11,19]. On the other hand, the magnitude of clinical improvements appeared to be in the range of those obtained with other regenerative materials such as a recombinant plateletderived growth factor (rhPDGF BB) on a β-TCP carrier, an enamel matrix protein derivative alone or guided tissue regeneration either alone or combined with grafting materials [20][21][22][23][24][25][26][27]. Furthermore, it is also important to note that the results observed in the control group compare favorably with previous studies evaluating treatment of intrabony defects using flap surgery alone indicating that substantial clinical improvements may be achieved with this treatment modality if an optimal level of plaque control is maintained [21][22][23][26][27][28].…”
Section: Discussionsupporting
confidence: 81%
“…There are references in the literature stating the positive properties and effects of bioactive glass as allowing the formation of bone-tissue bond. 14 Bioactive glasses are hard, solid (non-porous) and can be regarded as a threedimensional silica (SiO 2 ) network. Silicon dioxide (also known as silicate) forms the main component.…”
mentioning
confidence: 99%
“…Other studies randomized showed that there is glass on apatite-layer formation, rich in calcium and phosphorus, similar to natural bone, that favoring lead bone-glass (Stavropoulos et al, 2003) and inducing colonization of bone cells (Gatti et al, 2006). Bioactive glasses have been associated with other compounds such as demineralized bovine bone (Stavropoulos et al), autogenous bone graft (Tadjoedin et al, 2000(Tadjoedin et al, , 2002Moreira-Gonzalez et al), calcium phosphate (Moon et al, 2006), enamel matrix derivative (Kuru et al, 2006), and resorbable polymers composed of lactic acid and glycolic acid (Lu et al, 2003;Leach et al, 2006). Oonish et al (2000) studied, in animals, bioactive glass, Glass-ceramic A-W and synthetic hydroxyapatite and concluded that bioactive glass showed the highest bone formation rates and degradation, suggesting bone formation rates is proportional to particles dissolution, which favor the osteoblastics action.…”
Section: Resultsmentioning
confidence: 99%